An investigation into the potential of a nudging intervention model and implementation framework to alleviate academic amotivation in first-year undergraduate students. - Gillis, Peter Augustine (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2025)
Research shows lack of academic motivation as a major problem for undergraduates. Ultimately it can lead to multi-dimensional issues for, the student, the institution, and society. The negative form of motivation is amotivation. The focus of this study was to investigate the potential of an intervention model and supporting framework to provide targeted support for those affected by amotivation. A Design Based Research approach over three experiments, delivered targeted boost nudges to students, via text messages, based on their personal profiles. The intervention sought to alleviate amotivation. The final pre/post experiment with 117 students in a third level education institution in Ireland showed support for the concept at the amotivation level. Support was also shown for the ability of the intervention to impact targeted sub components of amotivation, negative beliefs around Value and Ability. Some support also emerged on the ability to impact real-world behaviours such as performance. The model and framework have shown potential to address what is understood to be a painful problem for today's students and society.
APPROVED
Keywords: Nudges; Ability; Maladaptive Behaviour; Self Determination Theory; Undergraduate; Academic Amotivation